Comparative Analysis of Service Quality in Enhancing Customer Satisfaction: A Study of ISO-Certified and Non-Certified Logistics Companies - Febrianto, Abi Sopyan; Inayati, Tutik; Hernawan, Yosep; Miftahuddin, Asep (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2025)
This study aims to analyze and compare the influence of service quality on customer satisfaction between logistics companies certified under ISO 9001:2015 (Ninja Xpress) and those not certified under ISO 9001:2015 (Pahala Express). The study employed a quantitative approach using an Independent Sample t-test. Data were collected through questionnaires involving 105 respondents who had used the delivery services of both companies. The findings indicate a significant difference in customer satisfaction levels between Ninja Xpress and Pahala Express. The sig. (2-tailed) value of < 0.001 suggests that Ninja Xpress, as an ISO 9001:2015 certified company, has a higher level of customer satisfaction compared to Pahala Express. The mean difference value of 0.19810 reflects a substantial average difference in customer satisfaction. These results confirm that ISO certification has a positive impact on service quality, which in turn contributes to increased customer satisfaction. The study recommends that logistics companies consider implementing ISO 9001:2015 standards as a strategy to enhance service quality and customer satisfaction, while also emphasizing the importance of comprehensive service quality improvement regardless of certification status.